Challenges of Illegal Trade and Law Enforcement in the Export Policy of Lobster Seeds - Darti, Andi; Saptomo , Ade (Journal of Comprehensive Science, 2024)
The Indonesian government, through the Ministry of Marine Affairs and Fisheries, reopened the export of lobster seeds (BBL) in March 2024 after previously being halted in 2021. This policy aims to improve the welfare of fishermen and contribute to national revenue. However, challenges such as the smuggling of BBL, both through legal and illegal channels, remain a significant issue. Therefore, cooperation between the government, traditional fishermen, aquaculture companies, and Commission IV of the Indonesian House of Representatives (DPR RI) is needed to address the challenges of illegal trade and law enforcement, as well as to create an efficient and sustainable system. This research aims to analyze the challenges in combating illegal trade and enforcing laws, as well as the oversight policies and sanctions related to the reopening of BBL exports in Indonesia. The research method used is a mixed approach, involving literature reviews and interviews. The findings show that the reopening of the lobster seed export policy under Regulation No. 7 of 2024 has led to an increase in BBL smuggling. Strong cooperation is expected to effectively address these challenges, ensuring that the goals of the export policy are achieved without harming any stakeholders.